Reproduction’s medicalization: ethical questions regarding technoscience impacts on the feminine body - Soares Parente, Flávia; Monteiro Dall’Olio, Adriana Maria; Cavalcante Teixeira, Leônia (O Mundo da Saúde, 2006)
The feminine body, in its sexual/reproductive function, has been the object of regulating policies that seek its normatization. With science and technology development, we see a manipulated body, controlled and monitored by biomedicine that determines the norms of health and disease, delineating lifestyles in social imaginary. Now, we see biomedical discourse strongly intervening as an instance producing norms and assigning meanings to the body, to sexuality and maternity, as it happens in the modern conception forms by means of the New Conceptive-Reproductive Technologies — NCRT. The present study aimed to investigate the several ethical aspects related to human reproduction in terms of biomedical intervention, taking as references anthropology, sociology, biomedicine and psychoanalysis. We consider the implications of that procedure to affect the singular and collective experiences linked to experiencing the body, sexuality and social and loving relationships. Bioethics-based reflections, by not intending to give conclusive answers to human dilemmas, establish reception spaces to unusual subjectivities made possible by technoscientific interventions. We emphasize the importance of conjoining perspectives that add to biomedical hegemony historical and subjective aspects considering humans complexity. Ethical concerns related to medicalized reproduction can promote dialogues that illuminate researches and interventions in life sciences interdisciplinary fields.